Transforming B2B Customer Experience Through Digital Transformation and Social Media in the Sudanese ICT Sector - Wafa Hamid Abdelrahman Mohamed Ahmed (SAN Scientific, 2025)
Customer experience (CX) is currently the strategic enabler for business-to-business (B2B) firms in today’s fast-changing digital economy. This study examines the synergistic impact of digital transformation (DT) and social media engagement (SM) on CX performance in Sudan’s information and communication technology (ICT) industry. Drawing on TAM, Sociotechnical Systems Theory, and Customer Experience Management theories, the research employs a mixed-methods design, collecting data from 231 questionnaires and 47 interviews in Khartoum’s digital hotspots. Quantitative results demonstrate that DT is a significant driver of operational effectiveness and mediates the SM–CX relationship, enhancing engagement and satisfaction when strategically used. Qualitative findings pinpoint leadership gaps, competency deficiencies, and demographic differences as drivers of digital responsiveness. Grounded in a conceptual framework with demonstrated reliability (Cronbach’s Alpha = 0.884), the study provides ICT firms and policymakers with pragmatic prescriptions, convergent digital solutions, inclusive skill development, and customer-focused innovation to support sustainable development in emerging economies.